EVALUATION OF A PROSPECTIVE COHORT STUDY DESIGN OF TRAINING LOAD RISK FACTORS FOR INJURY IN ELITE JUNIOR AUSTRALIAN FOOTBALLERS. Issue 7 (11th March 2014) - Lathlean, T; Stevenson, M; Gastin, P; Finch, C
Abstract : Background: Research focused on elite senior Australian Football (AF) competition, during the in-season, has found training load (a measurement of both training intensity and duration) and factors such as cumulative load, monotony and strain to be associated with injury risk. Little is known about whether player training loads in elite junior footballers during a pre-season also predispose players to the risk of injury. Objective: To explore pre-season training load risk factors for injury in elite junior Australian football players. Design: An Australian Football prospective cohort study is currently underway to assess risk factors for injury over the course of the 2014 elite junior, Victorian state league competition (TAC Cup) season. Training load risk factors of weekly cumulative load, monotony and strain will be assessed over the course of the general and specific conditioning phases of the pre-season period of the 2014 TAC Cup season. Setting: Elite junior AF. Participants: Players, conditioning and medical staff involved with the Victorian elite junior competition (TAC Cup). Up to 480 participants, across 12 clubs, will be involved in this cohort study. Interventions: Not applicable. Main outcome measurements: Number of new injuries across 40 weeks of training and 17 matches (rated as per 1000 training and playing hours), number of training sessions missed per injury and injury site, cause and mechanism. Results: Specific training load risk factors (cumulative training load, monotony and strain) will be identified over the course of the TAC Cup season as to their association with the number of new injuries and missed training sessions. Conclusions: This study aims to inform the pre-season conditioning of under-18 elite athletes in terms of both player load management and awareness of factors that could optimise player recovery, with the ultimate goal of resulting in fewer new injuries.